PENGEMBANGAN MEDIA PEMBELAJARAN BOARD GAME JUMANJI BERBASIS KERAGAMAN BUDAYA DENGAN INTEGRASI MODEL TGT (TEAMS GAMES TOURNAMENT) PADA PEMBELAJARAN MATEMATIKA SISWA KELAS III SEKOLAH DASAR - Aprilia Anggraini, Firsa; Sri Maruti, Endang; Ma'rufah Rohmanurmeta, Fauzatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of students' understanding of the material on plane geometry elements and the limited use of innovative and interactive learning media in elementary school mathematics learning. This condition can cause some students to tend to be less active, bored, and have problems understanding learning concepts. The research conducted has the aim of developing a Jumanji Board Game learning media based on cultural diversity integrated with the Teams Games Tournament (TGT) model, and to determine the level of validity, practicality, and effectiveness of the developed learning media. The research conducted uses the R&D method using the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research was conducted at SDN Sugihwaras 1 with 20 third-grade students as research subjects. Data collection techniques were carried out through observation, interviews, validation sheets, response questionnaires, and learning outcome tests. The results showed that the Jumanji Board Game media based on cultural diversity obtained a very valid category with a validation percentage of media experts of 92.63%, material experts of 85.33%, and language experts of 100%. The media was also deemed highly practical, based on 94.29% teacher responses and 90% student responses. Furthermore, the media proved effective in improving student learning outcomes, as demonstrated by an increase in the average pretest score from 64.93 to 95.20 on the posttest. Therefore, the Jumanji Board Game media, based on cultural diversity and integrated with the TGT model, is suitable for use as a mathematics learning medium because it can increase student understanding, motivation, activeness, and engagement in the learning process